The effect of isovalent substitutions and dopants of 3d-metals on the properties of ferroelectricssemiconductors - V'yunov, O.I.; Kovalenko, L.L.; Belous, A.G. (Condensed Matter Physics, 2003)
Electrophysical properties and microstructure of PTCR ceramics of the system (Ba,Ca,Sr,Y)TiO3 + y%Mn have been investigated. It has been shown that manganese ions increase the potential barrier at grain boundaries and form a high-resistance outer layer in (Ba,Ca,Sr,Y)TiO₃ ceramics. The resistance of grains, outer layers and grain boundaries, the values of temperature coefficient of resistance as well as the varistor effect as a function of manganese content of PTCR materials have been investigated.